Nilai-nilai Moral dalam Antologi Cerpen Filosofi Kopi karya Dewi Lestari - Elmikasari, Yoma (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The aim of this research is to identify and find the moral values that is contained in short story anthology book of Filosofi Kopi through the hermeneutic study and the implication in the study of literature appreciation in Senior High School. To reach the aim, the research use qualitative descriptive method through contain analysis, it is found that there are 7 aspects of positive moral values, they are: analysis based on moral values that reflect good attitude (1) Honest, (2) Responsible, (3) Loyal, (4) Polite, (5) Conscience, (6) Low Profile, (7) Consequence. The result of the whole research, there are 7 moral values  both positive  and negative in short anthology book Filosofi Kopi from Dewi Lestari, they are 1) Fourteen honest, 2) Thirty two responsible, 3) Thirty nine loyal, 4) Six polite, 5) Sixteen conscience, 6) Eight low profile, 7) Eighteen consequence. The implication of research result is the study of short story appreciation   in the school by using some titles in a short anthology book Filosofi Kopi from Dewi Lestari as source of study that has a potential to obtain the students who  have good moral values. Students who have good moral values can take the nation and the country will be better.